The two way symmetrical public relations and digital communication technologies: Between theory and praxis - Milojević, Ana (CM: Communication and Media ISSN 2466-541X; 2466-5452 (Online), 2016)
This article discusses how PR profession adapts to the new communication technologies, namely the potential of social media for establishing reciprocal relations between clients and publics. Methodologically based on a literature review, article aims to answer the research question: whether and to what extent the digital communication platforms are used for realization of the normative ideal – the two-way symmetrical model? Two-way symmetrical PR is equivalent to the strategic management function, which is defined as managing communication with publics in order to build long term relationships with stakeholders that may affect the organization or are most affected by the organization. The public relations help the organization to establish dialog with its stakeholders in order to accomplish the organization’s mission and to behave in a socially responsible manner. This article concludes that the capacity of digital media for realization of the two-way symmetrical relationships between organizations and publics is underutilized. Therefore, strategic management function can be still considered as highly normative PR model, despite the numerous studies that show its excellence. Inertia is rooted within the organizational structures as well as prevalent behavioral patterns of PR professionals.